Safavid conflict Uzbek 1524-1576 AD (Journal of the College of Basic Education, 2022)
The research Safavid relations with Uzbek during the reign of Shah Tahmasp I 1524-1576m, what happened during the reign of the events and the intensification of the conflict between the Safavids and the Uzbeks, and the principle of this conflict, at first during the reign of Shah Ismail, the first in 1510 and the evolution of this conflict into a power struggle and the control of an expansionary economic, During the reign of Shah Tahmasp intensified this conflict reached its peak in 1527 when defeated the Safavids in the battle against the Uzbeks Jam, have not stopped the attacks but said unity after this period up to the year 1555.Find the Safavid state's relations with the Turkmen tribes and warlords algorithm as well as eating, and the attempts by some princes of Uzbeks to improve relations with the Safavids, the fact that the Safavids after Magistrate Amasya with the Ottoman Empire Tafrgua to deter attacks Uzbeks full force and vigor.